Plan de mejora de la calidad en la prestación del servicio de agendamiento en una empresa de la ciudad de Bogotá D.C. (2016)
Alliance Disan UT., Is a nationwide company that offers a comprehensive care program for HIV-AIDS patients belonging to the Colombian National Army. Its objective is the provision of a service that contributes to the improvement of the health of all patients since their admission to the program, the delivery of the medication and their adherence. In this monograph we present the plan for improving the quality of the appointment scheduling service in a company in the city of Bogotá D.C. For the development of the plan, a review of the literature on the subject under study was carried out in the first stage, followed by a diagnosis of the company's situation using semi-structured interviews, both with the leader of the process and with the Other participants of the organization, likewise, a cause-effect diagram was drawn up in which the causes of the problem were identified.